QSFN: QoS-aware fog node provisioning in fog computing. (6th October 2022) - Chandak, Ashish Virendra; Ray, Niranjan Kumar; Puthal, Deepak
The quantity of IoT gadgets is consistently expanding and these gadgets are delay-sensitive and require a speedy reaction. These gadgets are connected with a cloud for the computation of requests yet there may be a delay in computation. To beat the present circumstance, fog nodes are kept at the edge of the IoT gadgets to perform the speedy calculation for delay-delicate applications. IoT devices generate a tremendous number of tasks and if the task number is increased then the number of fog nodes needs to be increased for immediate processing. Here, QoS-aware Fog Node (QSFN) provisioning algorithm has been proposed in which the number of fog nodes is automatically increased based on CPU utilisation, queue length and the number of available resources. We evaluate the performance of QSFN provisioning with Bee Swarm and Concurrent algorithm based on makespan, average execution, flowtime, success execution rate and average response time.